Hubungan Antara Trombositpoenia Dengan IgM, IgG Pada Pasien Demam Berdarah Dengue di Puskesmas Polowijen: The Relationship Between Thrombocytopenia And IgM, IgG In Dengue Fever Patients At Polowijen Community Health Center - Rodolof, Claudya Putri; Mahtuti, Erni Yohani; Rahmawati, Previta Zeizar (Borneo Journal of Medical Laboratory Technology, 2024)
Dengue hemorrhagic fever (DHF) caused by the dengue virus with general symptoms of fever, joint pain, rash and thrombocytopenia. One of the tests of the immune system in DHF is IgM and IgG. The purpose o determine the relationship between thrombocytopenia and (IgM) and (IgG) in patients with dengue hemorrhagic fever at the Polowijen Health Center in Malang City. The method is in the form of laboratory descriptive observational, carried out from May to June 2023. sampling by Accidental Sampling with a total of 25 patients. The results of the study of 25 patients with dengue hemorrhagic fever, 13 female patients (52%) and 12 male patients (48%). Based on the age category, there were 4 patients with dengue hemorrhagic fever under five (16%), children 10 patients (40%), adolescents 4 patients (16%) and early adults 7 patients (28%). The results of the infection category included primary 8 patients (32%), secondary infection 17 (68%). The results of data analysis with Pearson correlation showed a relationship between thrombocytopenia and IgM p = 0.029 r = 0.436 meaning that there is a strong and unidirectional relationship between thrombocytopenia and IgM. Thrombocytopenia with IgG p = 0.056 r = 0.387 means that there is a strong and unidirectional relationship between thrombocytopenia and IgG. The relationship between IgM and IgG is p = 0.093 r = -0.343. Which means that between IgM and IgG there is a strong inverse relationship, that is, if IgM is positive then IgG is negative, and vice versa